A Numerical Study of Brace-Viscous Damper System of Fixed Offshore Jacket Platforms Under Extreme Environmental Loads - M. A. Alwashali, SalahAldeen; Chin, Siew Choo (International Journal of Integrated Engineering, 2023)
The Persian Gulf is one of the most common regions where offshore platforms exist due to the presence of oil and natural gas. Wind, current, and wave loading affect the dynamic response of offshore structures, increasing performance uncertainty and catastrophic failure probability. Thus, this study investigates energy dissipation systems, particularly viscous dampers, to solve design and rehabilitation problems of fixed offshore structures. Viscos dampers improve vibrational behaviour and reduce structural response to optimise platform performance. Thus, eliminating costly structural repairs and strengthening components under extreme environmental loads extends structure lifetime. Thus, different viscous damper system configurations are tested to reduce dynamic response under extreme environmental loads in the Persian Gulf. Diagonal and inverted V-shaped brace viscous dampers with nine different arrangements are compared to find the best configuration. The study found that the brace viscous dampers with only three applied dampers at the top three levels are most efficient at mitigating dynamic response. It reduced displacements from level 1 to level 5 by 52% to 64% and connection stresses by 38% to 54%. Finally, viscous dampers reduce structural vibration and provide uniform and constant structural dynamic response, so the oil and gas industry should use them for offshore structure design and rehabilitation.